2018
DOI: 10.3892/etm.2018.6975
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the osteogenic capacity of human mesenchymal stem cells from bone marrow and umbilical cord tissue

Abstract: Mesenchymal stem cells (MSCs) have been extensively investigated in the field of regenerative medicine. Human bone MSCs (BMSCs) have become a common type of seed cell for bone tissue engineering. However, the viability and cell number of BMSCs are negatively correlated with donor age, and as the extraction process is painful, this method has not been widely used. As human umbilical cord MSCs (UCMSCs) may be harvested inexpensively and inexhaustibly, the present study evaluated and compared the regenerative pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…BMP-4, an osteogenic signaling molecule, having critical role in bone development,44 was majorly expressed in BM-MSC-laden composites.WJ-MSCs showed minimal osteogenic expression for all markers tested. Our results are largely in accordance with the literature in terms of the extent of osteogenesis reported in the order of BM-MSCs > AD-MSCs > WJ-MSCs (Figure 4B) 14,45,46. 3.2.5 | Immunofluorescence analysisMarkers spanning the different stages of osteogenesis, including early (COL I), mid (β-CATENIN), late (OCN, and osteocytic (SOST) differentiation, were analyzed for protein synthesis in cell-laden composites using immunofluorescence staining (Figure 4B).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…BMP-4, an osteogenic signaling molecule, having critical role in bone development,44 was majorly expressed in BM-MSC-laden composites.WJ-MSCs showed minimal osteogenic expression for all markers tested. Our results are largely in accordance with the literature in terms of the extent of osteogenesis reported in the order of BM-MSCs > AD-MSCs > WJ-MSCs (Figure 4B) 14,45,46. 3.2.5 | Immunofluorescence analysisMarkers spanning the different stages of osteogenesis, including early (COL I), mid (β-CATENIN), late (OCN, and osteocytic (SOST) differentiation, were analyzed for protein synthesis in cell-laden composites using immunofluorescence staining (Figure 4B).…”
supporting
confidence: 92%
“…Our results are largely in accordance with the literature in terms of the extent of osteogenesis reported in the order of BM‐MSCs > AD‐MSCs > WJ‐MSCs (Figure 4B). 14,45,46 …”
Section: Resultsmentioning
confidence: 99%
“…Bone engineering makes refractory bone defect reconstruction feasible and the key lies in the selection of seed cells . Multiple studies have demonstrated that SMSCs possess the extensive proliferative ability and multilineage differentiation potential . Our current study demonstrated that SMSCs were similar to other stem cells in terms of immunophenotypes and could be differentiated into osteoblasts in vitro.…”
Section: Discussionsupporting
confidence: 53%
“…31,32 Multiple studies have demonstrated that SMSCs possess the extensive proliferative ability and multilineage differentiation potential. 33,34 Our current study demonstrated that SMSCs were similar to other stem cells in terms of immunophenotypes and could be differentiated into osteoblasts in vitro. Thus, the acceleration of osteogenesis by the SMSCs is valuable for improving bone formation in bone engineering.…”
Section: Discussionsupporting
confidence: 51%
“…BM-MSCs, on the other hand, are considered the gold standard for cellular regenerative therapy and can be harvested from multiple donor sites in relatively large numbers. This means minimum need for expansion and versatility of applications including banking for future use [ 97 ] and both cell types have shown immune modulatory characteristics [ 98 , 99 , 100 ]. Therefore, both will be covered in the next sections.…”
Section: Tissue Engineering and Periodontal Regenerationmentioning
confidence: 99%